2022
DOI: 10.1021/acsearthspacechem.2c00008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amino Acids from Aldehydes and Ammonia: Implications for Organic Reactions in Carbonaceous Chondrite Parent Bodies

Abstract: The Strecker cyanohydrin synthesis is a known mechanism for the formation of amino acids from aldehydes, ammonia, and cyanide. An alternative mechanism for amino acid synthesis called the ammonia-involved formose-like reaction uses aldehydes and ammonia, and it has been demonstrated to explain the amino acid distributions in carbonaceous meteorites. In this study, experiments were performed to synthesize amino acids from 13C-labeled aldehydes and ammonia and to investigate the detailed formation pathways of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…In addition to glycine, d -alanine, sarcosine, d -aspartic acid, and β-alanine are also formed, which may be the result of the reaction of carbohydrates present in the analogue with ammonia or methylamine (Figure ). ,, This scenario is strengthened by kinetic profiles that show the involvement of carbohydrates in amino-acid formation from a formaldehyde mixture at high temperatures . A rapid increase in amino acid formation is also observed, followed by a rapid decrease of amino-acid abundance in the same time range as observed in our experiment.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to glycine, d -alanine, sarcosine, d -aspartic acid, and β-alanine are also formed, which may be the result of the reaction of carbohydrates present in the analogue with ammonia or methylamine (Figure ). ,, This scenario is strengthened by kinetic profiles that show the involvement of carbohydrates in amino-acid formation from a formaldehyde mixture at high temperatures . A rapid increase in amino acid formation is also observed, followed by a rapid decrease of amino-acid abundance in the same time range as observed in our experiment.…”
Section: Discussionsupporting
confidence: 81%
“…In the same methanol extract of the Murchison meteorite, N-containing heterocyclic compounds including alkylated pyridines and imidazoles were predominantly present as positive ions, which could be synthesized from formaldehyde and ammonia . It is also known that formaldehyde is an essential starting material to produce key prebiotic organic compounds including amino acids, which have been reported from various classes of meteorites. In addition, meteoritic IOM might be synthesized by the polymerization of formaldehyde. , Therefore, formaldehyde should play a central role in chemical evolution in primitive asteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these pathways are unfeasible to explain synthesis in meteorite parent bodies. It also remains an open question if alternatives proposed to the Strecker synthesis involving oxygen [91] are plausible in meteorite parent bodies. Dowler et al [92] and Friedmann & Miller [93] demonstrated prebiotic pathways toward vitamin B3 involving precursors formed by electrical discharges.…”
Section: Reaction Pathwaymentioning
confidence: 99%